COMBATE EXPERIMENTAL Ã€S NINFAS DO â€œALEURODÃDEO DA LARANJEIRAâ€ - Mariconi, Francisco A. M.; Sanada, Waldemar T.; Pulz, FÃ¡bio S.; Idagawa, Tolentino; Murai, Nelson Tozzi (REVISTA DE AGRICULTURA, 2016)
COMBATE EXPERIMENTAL Ã€S NINFAS DO â€œALEURODÃDEO DA LARANJEIRAâ€